The Effect of Disclosure of GHG Emissions (Greenhouse Gas), Carbon Performance, and Company Age on Company Value - Aisyah Qurratul AINI; Titik ARYATI (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to examine the effct of GHG Emission Disclosure (Greengas House), Carbon Performance, and Company Age on Firm Value. The data used is secondary data obtained from the Indonesia Stock Exchange in the form of financial reports, annual reports, and company sustainability reports. The sampling technique uses a purposive sampling approach, namely by using a sampling method based on certain criteria set by the researcher. The data analysis technique was carried out using multiple regression analysis using the SPSS 29.0 application. This study uses energy sector companies listed on the Indonesia Stock Exchange for the period 2021-2023, totalling 86 samples. The results of hypothesis testing conducted in this study indicate that GHG Emission Disclosure and Company Age has no effect on Firm Value. Meanwhile, Carbon Performance has an effect on Firm Value